CHANGE ANALYSIS OF ANTARCTIC ICE SHELVES BASED ON MULTIPLE REMOTE SENSING PRODUCTS - Y. Tian; H. Weng; D. Lv; X. Tong; R. Li (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2016)
The Antarctic ice sheet is well known as the most sensitive and key issue in the global climate change research and is playing a more and more important role for the global sea level change. Measurement of changes in area and mass of the Antarctic ice sheet is critically important and has been made by using different remote sensing technologies and ground exploration data. Sequential mapping of Antarctic boundaries provides a simple and direct method for measuring the area and volume if ice sheet or ice shelves advances or retreats in the Antarctic coasts. Our results show that the total ice shelf area is retreated between 1963 and 2009. However, the trend for each ice shelf is quite different.